Yosemite National Park : your complete hiking guide - Wenk, Elizabeth; Schaffer, Jeffrey P. (Wilderness Press, 2022)
"This comprehensive guide features almost every trail in Yosemite National Park and the surrounding areas, divided into 96 trips"--